The genome sequence of a bluebottle fly, Calliphora vicina (Linnaeus, 1758) [version 1; peer review: 2 approved] - Olga Sivell (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Calliphora vicina (bluebottle blow fly; Arthropoda; Insecta; Diptera; Calliphoridae). The genome sequence is 706.5 megabases in span. Most of the assembly is scaffolded into 6 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.72 kilobases in length. Gene annotation of this assembly on Ensembl identified 13,436 protein coding genes.